2017
DOI: 10.1021/acsmacrolett.7b00411
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Ring-Opening Polymerization of Amino-Acid-Derived N-Thiocarboxyanhydrides Toward Well-Defined Polypeptides

Abstract: Interfacial ring-opening polymerizations (iROP) of α-amino-acid derived N-thiocarboxyanhydrides (NTAs) in hexanes or heptane suspension using soluble primary amine initiators have been demonstrated to produce polypeptides with controlled molecular weight and low-tomoderate molecular weight distribution under mild conditions. The NTA monomers were shown to have significantly enhanced moisture and thermal stability relative to Ncarboxyanhydrides (NCAs), resulting in long shelf life and allowing the polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…However, there are two limitations in the use of NTAs for the polypeptide synthesis in terms of upscaling. First, dithiocarbonate used for the conversion of amino acids to the An attractive alternative method for the ROP of NCAs is the use of the sulfur-containing analogs of NCAs (Scheme 3) [9][10][11]. Amino acid N-thiocarboxyanhydrides (NTAs), which are synthesized using α-amino acids, undergo ROP in a manner similar to that of NCAs.…”
Section: Scheme 1 Ring-opening Polymerization (Rop) Of N-carboxyanhymentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are two limitations in the use of NTAs for the polypeptide synthesis in terms of upscaling. First, dithiocarbonate used for the conversion of amino acids to the An attractive alternative method for the ROP of NCAs is the use of the sulfur-containing analogs of NCAs (Scheme 3) [9][10][11]. Amino acid N-thiocarboxyanhydrides (NTAs), which are synthesized using α-amino acids, undergo ROP in a manner similar to that of NCAs.…”
Section: Scheme 1 Ring-opening Polymerization (Rop) Of N-carboxyanhymentioning
confidence: 99%
“…An alternative synthesis route to O-4-(nitrophenyl)urethane derivatives 1 is the reaction of amino acid tert-butyl ester with bis(4-nitrophenyl)carbonate (Scheme 6) [10]. The tert-butyl group of the resulting urethane is removed using trifluoroacetic acid to produce 1.…”
Section: Scheme 5 Synthesis Of the O-4-(nitrophenyl)urethane Derivatmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Amino acids N-thiocarboxyanhydrides (NTAs) are more stable monomers than NCAs [43][44][45][46] . Our group has reported that NTAs and their polymerizations tolerate mercaptans 47 , alcohols 48 , phenols 49 and water 50,51 .…”
mentioning
confidence: 99%